Normothermic Ex Vivo Kidney Perfusion Following Static Cold Storage—Brief, Intermediate, or Prolonged Perfusion for Optimal Renal Graft Reconditioning?. Issue 10 (8th May 2017) - Kaths, J. M.; Echeverri, J.; Linares, I.; Cen, J. Y.; Ganesh, S.; Hamar, M.; Urbanellis, P.; Yip, P.; John, R.; Bagli, D.; Mucsi, I.; Ghanekar, A.; et al.
Abstract : Normothermic ex vivo kidney perfusion (NEVKP) demonstrated superior results compared to hypothermic storage in donation after circulatory death (DCD) kidney transplantation. It is unknown whether an optimal perfusion time exists following hypothermic storage to allow for the recovery of renal grafts from cold ischemic injury. In a porcine model of DCD kidney autotransplantation, the impact of initial static cold storage (SCS) (8 h) followed by various periods of NEVKP recovery was investigated: group A, 8 hSCS only (control); group B, 8 hSCS + 1 hNEVKP (brief NEVKP); group C, 8 hSCS + 8 hNEVKP (intermediate NEVKP); and group D, 8 hSCS + 16 hNEVKP (prolonged NEVKP). All grafts were preserved and transplanted successfully. One animal in group D was sacrificed and excluded by postoperative day 3 due to hind limb paralysis, but demonstrated good renal function. Postoperative graft assessment during 8 days' follow‐up demonstrated lowest levels of peak serum creatinine for intermediate (C) and prolonged (D) NEVKP (p = 0.027). Histological assessment on day 8 demonstrated a significant difference in tubular injury (p = 0.001), with highest values for group B. These results suggest that longer periods of NEVKP following SCS are feasible and safe for postponing surgical transplant procedure and superior to brief NEVKP, reducing the damage caused during cold ischemic storage of renal grafts. Abstract : Prolonged versus brief normothermic ex vivo kidney perfusion following 8 hours of static cold storage demonstrates superior outcomes in a model of donation after circulatory death pig kidney transplantation.